RANCANG BANGUN APLIKASI GAME PUZZLE BERBASIS ANDROID (Information Technology and Telematics, 2015)
Abstract   Game defined as structured or semi-structured activity which generally use for pleasure and utilised. The key elements of a game are goals, rules and interactions that physical and spiritually stimulated the gamer. Few kind of game reputed can increase censoric and motoric ability, and has a function as medium of physical and spiritual practice. Puzzle Game is a kind of game that deeply challenge children’s creativity and memory because the motivation appeared to keep trying to solve problems, but in such a fun way because can be repeat over again. The challenge of this game will create narcotizing effects to keep trying until it works. This game can also be able to sharpen brain’s ability at logics/mathematics. The creation of this application use Android Development Tools (ADT)  Build  v.22  includes  Eclipse  Platform, Java Development Kit (JDK), Android Software Development Kit (Android SDK) and Adobe Photoshop Software Technics. Keyword : Game, Puzzle, Android